2010
DOI: 10.2527/jas.2009-2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to calves persistently infected with bovine viral diarrhea virus type 1b and subsequent infection with Mannheima haemolytica on clinical signs and immune variables: Model for bovine respiratory disease via viral and bacterial interaction1,2

Abstract: The objective was to determine effects of an intratracheal Mannheimia haemolytica challenge after 72-h exposure to bovine viral diarrhea virus type 1b (BVDV1b) persistently infected (PI) calves on serum antibody production, white blood cell count (WBC), cytokine concentrations, and blood gases in feedlot steers. Twenty-four steers (initial BW = 314 +/- 31 kg) were randomly allocated to 1 of 4 treatments (6 steers/treatment) arranged as a 2 x 2 factorial. Treatments were 1) steers not exposed to steers PI with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 39 publications
9
60
0
Order By: Relevance
“…Horadagoda et al (1999) measured a-GP, Hp, and SAA in 81 cattle that were diagnosed with acute or chronic inflammation, each from a number of different causes, and concluded that SAA and Hp would be the most valuable for discrimination between acute and chronic inflammation. Research in this area relative to feedlot cattle has foeused on serum Hp and SAA concentrations (Wittum et al, 1996;Carter et al, 2002;Burciaga-Robles et al, 2010b). Serum Hp has been shown to increase in response to experimental infection with M haemolytica (Conner et al, 1989;Burciaga-Robles et al, 2010b) or BVDV (Gânheim et al, 2003).…”
Section: Acute Phase Immune Responsementioning
confidence: 97%
“…Horadagoda et al (1999) measured a-GP, Hp, and SAA in 81 cattle that were diagnosed with acute or chronic inflammation, each from a number of different causes, and concluded that SAA and Hp would be the most valuable for discrimination between acute and chronic inflammation. Research in this area relative to feedlot cattle has foeused on serum Hp and SAA concentrations (Wittum et al, 1996;Carter et al, 2002;Burciaga-Robles et al, 2010b). Serum Hp has been shown to increase in response to experimental infection with M haemolytica (Conner et al, 1989;Burciaga-Robles et al, 2010b) or BVDV (Gânheim et al, 2003).…”
Section: Acute Phase Immune Responsementioning
confidence: 97%
“…45 Based on an infection trial, exposure to persistently infected steers with bovine viral diarrhea virus resulted in significantly less WBC and neutrophils, whereas inoculation with Mannheimia haemolytica resulted in greater WBC and neutrophils. 39 Lymphocyte count decreased with exposure to persistently infected animals and M haemolytica. 39 In another infection trial, 42 WBC and segmented neutrophils increased on day 1 after infection with M haemolytica, but decreased to baseline thereafter.…”
Section: White Blood Cell Countmentioning
confidence: 98%
“…39 Lymphocyte count decreased with exposure to persistently infected animals and M haemolytica. 39 In another infection trial, 42 WBC and segmented neutrophils increased on day 1 after infection with M haemolytica, but decreased to baseline thereafter. Neutrophil/lymphocyte ratio and WBC were compared with a clinical illness score and rectal temperature in naturally occurring BRD outbreaks.…”
Section: White Blood Cell Countmentioning
confidence: 98%
“…The evidence that BHV-1 and BVDV negatively affect humoral immune responses has been previously reviewed. 22,33,193 The bacterial pathogens causing BRD have several mechanisms to limit antibody-mediated immunity, although it should be emphasized that induction of humoral immunity does confer protection in challenge models of the disease. The capsule of M. haemolytica confers partial resistance to antibody, whereas an acapsular mutant had similar sensitivity to complement as the parent strain.…”
Section: Effects Of Predisposing Factors On Antibody Defensesmentioning
confidence: 99%